SALAM Senawang Specialist Hospital / Fatin Nuraliah Mohd Shukur - Mohd Shukur, Fatin Nuraliah (Faculty of Business and Management, 2023)
According to the course outline, MGT666 internship is the final course for all students who study m the Faculty of Business Management. I started my very first internship was at the SALAM Senawang Specialist Hospital in Negeri Sembilan. It was fun experience and I feel very happy to be able to do my internship there at SALAM Hospital. 1 have gathered as an intern in the finance department at SALAM Senawang Specialist Hospital from 1st March 2023 until 15 August 2023. My main objective in this internship is to learn as much as I can so that I can use it in my future job. Being hired as a finance trainee at SALAM Senawang really helped me to understand more about my course, and I can use my knowledge during training. A healthcare organization called SALAM Senawang offers access services and medical services to the residents of Senawang and the surrounding area. Senawang Indah Medical Center Sdn. Bhd. was the name of this hospital before it was changed to SAL.AM Senawang Specialist Hospital. This report discusses the history of SALAM Senawang, including company's objective, services and organization structure and value. This report also consists of SWOT analysis SALAM Senawang, which is emphasizing on the firm's strengths, weaknesses, opportunities and threats as well as my ideas and recommendation based on analysis.